MAQSUD SHAYKHZODA IS A VERSATILE TALENT (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
The work is politically charged that the past is idealized. The confiscated items included a manuscript of the drama. After the author was acquitted and returned, certain organizations did not return the manuscript on the pretext that it was “lost”. This article spoke about the importance of the work of Maqsud Shaykhzoda in the education of young people, such qualities as courage, fairness, thoughtful thinking, popularism, expressed in the image of the heroes of the work in Uzbek literature.